Method for in situ analysis of volatiles generated during cure of composites. (August 2019) - Lo, Jonathan; Nutt, Steven
Abstract: Conventional epoxies used in composites are formulated to release minimal amounts of volatiles during cure, aside from moisture, which is a perpetual concern. However, a variety of polymers are used in production of composite parts, including adhesives, prepregs, and non-epoxy polymers, and sources of volatilization during processing can be both difficult to determine and problematic. Here we demonstrate a general method for in situ analysis of volatile release during cure. The method improves upon traditional characterization techniques of TGA/MS and TGA/FTIR (thermogravimetric analysis, mass spectroscopy, and Fourier transform infra-red spectroscopy). We characterize a commercial epoxy prepreg typical of those used in aerospace, a benzoxazine/epoxy blended liquid resin intended for high-temperature service, and finally, a high-temperature polyimide. By understanding the identity, origin, and kinetics of volatile release in these three materials, we can prescribe additional pre-treatments and define process windows to minimize and even eliminate volatile-induced porosity. Finally, we demonstrate the utility of the reaction cell/FTIR approach for characterizing cure-induced volatiles and mitigating final part porosity.